The first elegy of Maximianus: A translation and commentary based on an analysis of possible earlier Latin influences found by a computer search on the PHI CD-ROM disk. - Tyson, Margaret. (University of Ottawa (Canada), 1997)
This thesis comprises an assessment of the introductory poem of a book of six, known as the "first elegy by Maximianus". The authorship of the poem is uncertain, and a principal objective of the study is to shed light on this puzzle. A review of the poem's quality and its historical context leads to the thesis that it could have been authored as a school exercise by one or a group of students of Latin literature writing in the 6th century A.D. The influence of earlier writers on the composition of the poem has been examined by performing a thorough search through classical Latin literature for phrases that are similar to those found in this "first elegy by Maximianus". Such a study would have been prohibitively time-consuming until recently, when the introduction of high-speed computers has made the exercise feasible. In the present work, the PHI CD-ROM collection of the complete Republican and early Imperial Latin literature was used as the primary reference for phrase-matching. A methodology has been developed and described for classifying the probability of earlier influence on phrases in the poem. A complete translation of the poem is followed by a commentary on the influence of previous writings on phrases in the first 220 lines of the poem that have been found in the course of the computer search to be similar to phrases used by previous authors. It is shown that 62 phrases and half-lines are likely to have been influenced by the Latin literature of the period from 250 B.C. to 200 A.D. The evidence is consistent with the suggestion in this thesis that the elegy could have been a school exercise written by an immature student or group of students.
Keywords: Literature, Classical.